Karakteristik Kimia Tanah Gambut pada Tiga Tipe Penggunaan Lahan - Anggi Dwi Oktania; Ahmad Kurnain; Fakhrur Razie (Acta Solum, 2024)
Peat soil is a soil that has been decomposed by organic matter. Man-made peatlands have been converted into agricultural land. In addition to being turned into agricultural land, some peatlands are also not used, causing the land to turn into shrubs and causing land to burn because it is not managed by the owner. Peatlands therefore consist of various types of land use. Peat soils in different types of land use have different characteristics. The purpose of the study was to determine the differences in some of the chemical properties of peatlands that have been used for shrubs, open land, and agriculture. To see the differences in soil chemical properties on various land uses, descriptive analysis, and standard deviation are used by presenting bar charts. The soil pH content on agricultural land is higher. The C-organic content in shrubs is higher than in agricultural land. Ash content on agricultural land is higher. Dissolved organic carbon on agricultural land tends to be lower.